2023
DOI: 10.3390/plants12030460
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of Saussurea costus Extract against Bacteria, Candida, Herpes, and SARS-CoV-2

Abstract: Medicinal herbs have long been utilized to treat various diseases or to relieve the symptoms of some ailments for extended periods. The present investigation demonstrates the phytochemical profile, molecular docking, anti-Candida activity, and anti-viral activity of the Saussurea costus acetic acid extract. GC-MS analysis of the extract revealed the presence of 69 chemical compounds. The chemical compounds were alkaloids (4%), terpenoids (79%), phenolic compounds (4%), hydrocarbons (7%), and sterols (6%). Mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 92 publications
1
5
0
Order By: Relevance
“…Other studies have indicated that S. lappa extract has partial antiviral activity with effectiveness of 75%, 65%, and 13% against the SARS CoV-2/Wuhan strain B.1.36 at concentrations of 1/64, 1/128, and 1/256 [26]. While the toxicity test also showed that S. lappa ethanol extract had a CC50 of 131.4 μg/ml, this result was similar to previous reports that showed S. lappa ethanol extracts had a CC50 of 162.9 μg/ml [27] and 70.36±0.8 µg/ml [28]. The selectivity index (SI) for this study was 3.51 points.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have indicated that S. lappa extract has partial antiviral activity with effectiveness of 75%, 65%, and 13% against the SARS CoV-2/Wuhan strain B.1.36 at concentrations of 1/64, 1/128, and 1/256 [26]. While the toxicity test also showed that S. lappa ethanol extract had a CC50 of 131.4 μg/ml, this result was similar to previous reports that showed S. lappa ethanol extracts had a CC50 of 162.9 μg/ml [27] and 70.36±0.8 µg/ml [28]. The selectivity index (SI) for this study was 3.51 points.…”
Section: Discussionsupporting
confidence: 88%
“…By gathering full-scan mass spectra throughout the scan range of 35–500 amu, all data were obtained. Through comparison of the collected spectra with mass spectral libraries, the unidentified chemicals were found [ 52 ]. The determination of the calibration and minimum detection limits for the system was based on the manufacturing conditions, and the corresponding equation is available elsewhere [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Influenza is the upper respiratory tract disease, involving seasonal or climatic occurrences from avian and other zoonotic origins, causing global 3 to 5 million morbid cases annually (Krammer et al 2018 ). Previous and recent research shows a wide range of phytochemicals could prevent the influenza virus both in vitro (Eggers et al 2022 ; Yang et al 2022 ; Idriss et al 2023a , b ; Mothana et al 2006 ; Pantev et al 2006 ; Prajoubklang et al 2005 ) and in vivo (Ivanova et al 2005 ; Prahoveanu et al 1985 ). Moreover, flavonoids derived from aerial parts of Salvia plebeia were proven effective against influenza A (H1N1) neuraminidase, inhibiting the replication cycle (Bang et al 2016 ).…”
Section: Phytoactive Compounds For Influenzamentioning
confidence: 99%
“…Most of the anti-viral medicines have detrimental failures with long-term drug resistance. Various plants are valuable assets, which are to be explored, especially in emerging resistant infectious diseases (Idriss et al 2023a , b ; Mukhtar et al 2008 ). Undeniably, plant-derived phytoactive compounds are potential therapeutic metabolites with the power to obstruct, control viral uptake, attach to surface receptors, and compete for pathways of activation of intracellular signals (Mao et al 2022 ; Ghosh et al 2009 ; Kapoor et al 2017 ; Khan et al 2005 ; Mohapatra and Dar 2010 ).…”
Section: Introductionmentioning
confidence: 99%